The Effect Of Work Competency And Work Discipline On Employee Performance At Klari District Office - Erika Cahyani; Asep Jamaludin; Nandang (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This study aims to determine and analyze the partial and simultaneous effects of work competence and work discipline on the performance of employees of the Klari sub-district office. Research method— This type of research uses a quantitative approach and is conducted using a questionnaire method. The sample of this study amounted to 40 employees using the saturated total sampling formula. The analysis model used in this study is a multiple regression analysis model using the F test and t test. Result— The results of this study indicate that there is a partial effect of work competence on employee performance and a partial effect of work discipline on employee performance. Additionally, there is a simultaneous influence of work competence and work discipline on the performance of employees of the Klari sub-district office. Conclusion— The conclusion of this study is the importance of improving work competence and employee discipline to improve performance at the Klari District Office.